Harmonic assessment on two photovoltaic inverter modes and mathematical models on low voltage network power quality - Penangsang, Ontoseno; Wibowo, Rony Seto; Aryani, Ni Ketut; Prasetyo, Mario Dwi; Arianto, Marcel Nicky; Lutfi, Aulia Amjad (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Power quality is a crucial aspect of designing a large-scale photovoltaic power plant, particularly regarding harmonics caused by inverter switching. This research aimed to analyze harmonics in a system using electrical transient analyzer program (ETAP) Power Station 20.5.0 to uncover the effect of irradiance on the inverters’ power quality running at 85% and 100% power factors. We analyzed both voltage and current total harmonic distortion (THDi and THDv) from the simulation and compared them with the mathematical model. Moreover, we analyzed the effect of changes in irradiance level on harmonics and reactive power penetration, which influenced power losses in transformers and cables. Inverters at 85% power factor experienced an increase in THDi, whereas those at 100% power factor decreased. Inverters with 85% power factor experienced more frequent switching, causing more prominent distortion. The magnitude of THDv increased proportionally with the rise of irradiance level. Inverters at 85% had a higher THDv value because of the excessive reactive power compensation when irradiance rose. Irradiance level had an inverse relationship with system losses since high irradiance levels led to lower losses as less power was required through transmission lines and transformers. Moreover, losses at 85% power factor were higher since the high harmonics caused additional losses.